HUKUM BADAL HAJI MENURUT PANDANGAN MAJELIS TARJIH DAN TAJDID MUHAMMADIYAH DAN LAJNAH BAHTSUL MASAIL NAHDLATUL ULAMA - Makrus, A. (UIN Sunan Kalijaga Yogyakarta, 2018)
Islam provides dispensation for those who have not been able to meet these requirements not to perform the pilgrimage. Anyone who does not fulfill one of the pre-determined requirements, namely Islam, is reasonable, mature, independent, and capable, is not obliged to perform the pilgrimage. However, it is different with people who have been sick or died before having time to perform the pilgrimage in this case there is a difference of opinion among scholars. People who are sick or die and have more assets but are physically incapable of performing Hajj are replaced by other people called Badal Hajj. The Muhammadiyah Tarjih and Tajdid Council and Lajnah Bahtsul Masa'il Nahdlatul Ulama' differ in their views on the legal issue of hajj. The Tarjih Council and the Tajdid Muhammadiyah in their decision allowed Badal Hajj, because it adhered to the Hadith of the Khas'am tribe narrated by Ibn Abbas ra which stated that by delegating his pilgrimage to his children or relatives, he had to fulfill the mandatory Hajj requirements. Meanwhile, Lajnah Bahtsul Masail Nahdlatul Ulama decided on the permissibility of making other people's pilgrimages. The istinbat method always uses the opinions of previous scholars, so that the decisions are relevant to the opinions of previous scholars in their classical works. Lajnah Bathsul Masa'il Nahdlatul Ulama does not provide a limit on the badal of Hajj, and a person has the right to make another person's pilgrimage even though he is not from the family and must meet certain conditions, namely that he has performed Hajj first.